Analysis Impact System Information Accounting in Management MSME Finance in the District Langowan - Olviane Olke Sumampouw; Miryam Lonto (AIBPM Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy; however, financial management practices in rural areas, such as Langowan District, Minahasa Regency, remain constrained by manual bookkeeping systems and limited accounting literacy. This study aims to analyze the impact of Accounting Information System (AIS) implementation on the financial management of MSMEs by examining its influence on operational efficiency, financial reporting accuracy, and business decision-making. A mixed-methods approach was employed by integrating qualitative and quantitative methods through observations, interviews, and questionnaire surveys involving MSME owners operating in the agricultural, fisheries, and trade sectors. The findings indicate that AIS implementation has considerable potential to improve operational productivity, enhance the accuracy of financial reporting, and facilitate access to financing. Nevertheless, its adoption remains limited due to inadequate digital infrastructure and insufficient technical capabilities among MSME owners in Langowan District. The study concludes that strengthening digital infrastructure and improving digital and accounting literacy are essential to maximizing the benefits of AIS implementation. These findings provide practical implications for local governments and business stakeholders in designing strategies to accelerate MSME digital transformation, strengthen business competitiveness, and support the objectives of the National Proudly Made in Indonesia Movement (GNBBI).